PREVALENCE OF ORAL MUCOSAL LESION AMONG PATNA POPULATION – A SURVEY - DR BINU SINGH,; DR ARCHANA SUDHEER,; DR KUMAR ANAND,; DR SATYAPRAKASH,; DR BABITA KUMARI,; DR LIPI SINGH, (The Bioscan, 2026)
Oral mucosa is an effective protective barrier and is commonly affected by lesions that may be innocuous to those that are malignant. Aim of this study was to study the prevalence of oral mucosal lesions in Patna population. Out of 2500 subjects, 1585 were males and 915 were females. The maximum number of participants were in the age group of 25-34 years. Habit of Cigarette smoking was found in 160 subjects. In smokeless form, Khaini in 435 and Gutkha habit in 320 subjects were seen. Oral mucosal lesions were present in 950 of which 335 lesions were non-tobacco users and 615 subjects were tobacco users. Tobacco pouch keratosis was seen in 240 subjects (29.81%) followed by OSMF in 145 (18.01%) among tobacco users. Lichen planus was the most common oral mucosal lesion in 85 subjects (5.01%) among non-tobacco users. The study population is predominantly male. Smokeless tobacco, particularly Khaini and Gutkha, is a significant concern in this population, while smoking tobacco and alcohol consumption are less prevalent. The presence of lesions in over one-third of the participants highlights a potential health issue within this population. There is a strong relationship between tobacco use and the occurrence of oral mucosal lesions. Keywords Oral mucosal lesions, leukoplakia, oral submucous fibrosis, Malignant lesions.